Auld Lang Syne - Grant, M. J. (Open Book Publishers, 2021)
In Auld Lang Syne: A Song and its Culture, M. J. Grant explores the history of this iconic song, demonstrating how its association with ideas of fellowship, friendship and sociality has enabled it to become so significant for such a wide range of individuals and communities around the world. Intro – Contents – Introduction – Note on the Text – Acknowledgements – 1. Elements of a Theory of Song – 1.1 The Social Functions of Song – 1.2 The Songs Folk Sing: Some Historical Evidence – 1.3 Implied and Inherited Significance – 1.4 Auld Lang Syne as an Object of Research: Some Issues – The Tunes – The Words – The Traditions – 2. Auld Lang Syne: Context and Genesis – 2.1 Being a Short Discourse on Song in the Eighteenth Century – 2.2 Auld Lang Syne before Burns – FIRST PART – SECOND PART – 2.3 The Jacobite Songs – 3. Burns's Song – 3.1 Mrs Dunlop's Song – 3.2 Burns's Text – 3.3 Burns's Tune – 3.4 What Thomson Did – 3.5 From M1 to M2 – 3.6 The Legacy of the Old Songs and Two Contemporaries of the New – 4. Auld Lang Syne in the Early Nineteenth Century – 4.1
Description based on publisher supplied metadata and other sources
Keywords: Burns; Robert; 1759-1796; Songs; Scots; Electronic books